2020
DOI: 10.1016/j.clbc.2020.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of the Metaplastic Spindle Cell Carcinoma of the Breast Reveals Potentially Targetable Biomarkers

Abstract: Spindle cell carcinoma is a rare subtype of metaplastic breast cancer, with triple-negative phenotype. Twenty-three spindle cell carcinomas were comprehensively explored for biomarkers of immuno-oncology and targeted therapies using immunohistochemistry and DNA/RNA sequencing. Spindle cell carcinomas are characterized by targetable molecular alterations in the majority of cases, but, owing to the lack of uniform findings, individual patient profiling is necessary. Introduction: Spindle cell carcinoma is a rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…In one series, important age differences among histological subtypes were observed, MBC with chondroid differentiation occurring at a mean age of 71 years, whereas spindle and squamous cell carcinomas presented at mean ages of 56 and 48 years old, respectively [ 5 ]. MBC are usually large tumors with a mean size of 3.9 cm, among the series reviewed [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Most tumors present in stage II.…”
Section: Clinicopathological Featuresmentioning
confidence: 99%
See 3 more Smart Citations
“…In one series, important age differences among histological subtypes were observed, MBC with chondroid differentiation occurring at a mean age of 71 years, whereas spindle and squamous cell carcinomas presented at mean ages of 56 and 48 years old, respectively [ 5 ]. MBC are usually large tumors with a mean size of 3.9 cm, among the series reviewed [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Most tumors present in stage II.…”
Section: Clinicopathological Featuresmentioning
confidence: 99%
“…In this study, we reviewed 14 series [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 28 , 29 ] including a total of 539 molecularly characterized tumors. Eight series [ 5 , 6 , 9 , 10 , 11 , 15 , 29 , 30 ] included copy number variations (CNVs) data. The most frequent alterations are presented in Table S1 , which includes the specific results of all the studies.…”
Section: Molecular Alterationsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 However, HRAS mutations are not exclusive of adenomyoepitheliomas and have been reported in other breast tumors, including MBCs without a contiguous adenomyoepithelioma. 5 Krings et al 6 reported a HRAS mutation in a paired analysis of MBC and its associated ductal carcinoma in situ (DCIS). Therefore, the detection of HRAS mutations has no diagnostic implications in the absence of a morphological context.…”
mentioning
confidence: 99%